UMP celebrates volunteers watch Mat Kilau Kebangkitan Pahlawan - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 20 July 2022 - The Institute of Civilisation and Strategic Studies (ITKAS) of Universiti Malaysia Pahang (UMP) organised Program Menghayati Tamadun Pahang to celebrate 150 students, staff, KILAU UMP volunteers and media practitioners by watching the film Mat Kilau Kebangkitan Pahlawan at the East Coast Mall.